A 250‐Year European Drought Inventory Derived From Ensemble Hydrologic Modeling. Issue 11 (14th June 2019) - Moravec, Vojtěch; Markonis, Yannis; Rakovec, Oldrich; Kumar, Rohini; Hanel, Martin
Abstract: We present a 250‐year (1766–2015) inventory of European meteorological, hydrological, and agricultural droughts derived from ensemble simulations of the mesoscale Hydrological Model (mHM). The inventory of droughts takes into account an ensemble of 100 simulations from the hydrological model, allowing for assessment of how different meteorological forcing and model parameterizations affect a drought ranking. For the most extreme droughts, the variability in the ranking of drought events is low, while for the years with moderate precipitation deficits, the variability increases. Despite the underlying uncertainties, our drought inventory shows increased recurrence of soil moisture droughts in the Mediterranean and declining spatial extent of hydrological drought in Central Europe over the last three decades. Plain Language Summary: Drought is one of the most costly natural hazards. Complete understanding of this phenomenon evades us because drought needs a long period of time to evolve and when it does, it might propagate through different components of the hydrological cycle. For example, meteorological drought, which is a lack of rainfall, might result in hydrological drought (low discharge/lake levels), agricultural drought (low soil moisture), or both. This is why it is important to record past occurrences of individual droughts to better understand under what conditions they propagated. To address this, herein we produce a 250‐year long European drought inventory based on hydrological modeling that presents the interaction of the three types of drought, namely, meteorological, hydrological, and agricultural, as well as their properties in a single, comprehensive framework. Key Points: A 250‐year inventory depicts the major meteorological, hydrological, and agricultural droughts across Europe Visualization of ensemble allows for an effective comparison among major drought years (severity and spatial extent) Increased recurrence of soil moisture droughts across the Mediterranean in the recent decades